Teacher Strategies for Developing 4C Skills (Critical Thinking, Creativity, Communication, and Collaboration) in History Learning at SMAN 3 Tegal - Rizki Nur Fadhilah; Atno Atno (STKIP Taman Siswa Bima, 2025)
This study aims to analyze teachers’ strategies in fostering 4C skills (Critical Thinking, Creativity, Communication, and Collaboration) in history learning at SMAN 3 Tegal, and to explore the challenges and solutions in its implementation. The research is grounded in the 21st-century education demand for higher-order thinking skills, while history learning in Indonesia often remains memorization-oriented. Using a qualitative approach with a grounded theory design, data were collected through in-depth interviews with two history teachers, document analysis, and limited observation. Findings indicate that strategies include contextual learning, collaborative projects, cross-subject integration, and continuous reflection. Challenges such as limited facilities, time constraints, student readiness, and administrative workload were addressed through media innovation, project segmentation, socio-emotional approaches, and teacher collaboration. Although findings are context-specific and lack quantitative measurement, this study offers practical contributions to developing history learning models aligned with the Curiculum Merdeka and strengthening 21st-century skills.